Legend - Lu, Marie 1984- (New York Scholastic Inc., 2011)
In a dark future, when North America has split into two warring nations, fifteen-year-olds Day, a famous criminal, and prodigy June, the brilliant soldier hired to capture him, discover that they have a common enemy.
Keywords: Fugitives from justice -- Fiction; Criminals -- Fiction; Soldiers -- Fiction; War -- Fiction; Government, Resistance to -- Fiction; Plague -- Fiction